Effect of Solanum lyratum Polysaccharide on Malignant Behaviors of Lung Cancer Cells by Regulating the Circ_UHRF1/miR-513b-5p Axis - Feng, Yuyu; Wang, Wei; Liu, Conghui (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effect of Solanum lyratum polysaccharide on the malignant behavior of lung cancer cells and its possible mechanism. For this purpose, lung cancer A549 cells were cultured in vitro and treated with different doses (0.4, 0.8, 1.2 mg/mL) of Solanum lyratum polysaccharide for 24 h. Then cell proliferation was detected by the CCK-8 method and clone formation test. Transwell test was used to detect cell migration and invasion, and flow cytometry was used to detect cell apoptosis. The protein expressions of Bax and Bcl-2 in cells were detected by Western blotting, and the protein expressions of circ_UHRF1 and miR-513b-5p were detected by the qRT-PCR method. Pearson correlation was used to analyze the correlation between circ_UHRF1 and miR-513b-5p expressions in lung cancer tissues. Results showed that compared with the control group, the proliferation inhibition rate and apoptosis rate of A549 cells that intervened with the Solanum lyratum polysaccharide and expression of Bax protein in the cells were all increased (P<0.05), but the number of clones, migration and invasion and the protein expression of Bcl-2 were all decreased (P<0.05), and were dose-dependent. The expression of circ_UHRF1 in A549 cells that intervened with the S. lyratum polysaccharide was decreased (P<0.05), but the expression of miR-513b-5p was increased (P<0.05). The expression of circ_UHRF1 in lung cancer tissues was higher than that of adjacent tissues (P<0.05), and the expression of miR-513b-5p was lower than that of adjacent tissues (P<0.05). The expressions of circ_UHRF1 and miR-513b-5p in lung cancer tissues were negatively correlated (r=-0.861, P<0.05). Circ_UHRF1 could target miR-513b-5p, and the expression of miR-513b-5p in A549 cells knocking down circ_UHRF1 was increased. After knocking down circ_UHRF1, the proliferation inhibition rate and apoptosis rate of A549 cells and protein expression of Bax in the cells were all increased (P<0.05), but the number of clones, migration and invasion and the protein expression of Bcl-2 were all decreased (P<0.05). Up-regulation of circ_UHRF1 reduced the effects of S. lyratum polysaccharide on the proliferation, migration, invasion and apoptosis of A549 cells. In general, S. lyratum polysaccharide could inhibit the proliferation, migration and invasion of lung cancer A549 cells, and induce cell apoptosis. Its mechanism may be related to the regulation of the circ_UHRF1/miR-513b-5p axis.